Effects of hydrologic modifications to riparian plant communities in a large river system in northern China. Issue 3 (10th February 2015) - Xiu, Chen; Gerisch, Michael; Ilg, Christiane; Henle, Klaus; Ouyang, Zhiyun
Abstract: Hydrologic modifications to rivers caused by anthropogenic activity have major impacts on riparian ecosystems. Alterations to the hydrologic regime and their interactions with natural environmental parameters exert selective pressures on riparian vegetation, resulting in adaptations to specific flow attributes. However, few studies have attempted to detect these effects under multiple hydrologic conditions, especially for rivers in semi‐dry and semi‐humid regions. Using the "space‐for‐time substitution" method, we investigated the effects of hydrologic modifications to the riparian plant community along the Yongding River of northern China, by comparing community structure metrics (diversity, plant moisture affinity group, and lifespan) and a function metric (biomass) under three streamflows (perennial, seasonal and dried‐up). Among these streamflows, seasonal flow reaches had the greatest plant diversity. Responses of plant moisture group and lifespan were inconsistent in different hydrologic stages, although they varied significantly ( P < 0.01). Annuals and biennials greatly increased from perennial to seasonal streamflow (~59 %), while perennials decreased (~41 %). However, from seasonal to dried‐up flow, the percentage of mesics and xerics increased by 12.8 and 11.8 %, respectively, while hydrics decreased dramatically (by 24.6 %). Perennial flow had significantly greater aboveground biomass ( P < 0.05) than the other two flows. Hydrologic conditions and their related soil nutrients were the main driving factors of community structure and function, which explained 21.0 and 18.0 % of variation, respectively. These findings reveal the response process of the riparian plant community during hydrologic modification from perennial to dried‐up streamflow.